Design and realization of a fuzzy logic-based MPPT controller for PV systems using microcontroller - Mohan P. Thakre; Badal Kumar; Alok Kumar; Supriya Nilesh Thakur; Krupali Kanekar; Pranali M. Thakre; Prashant K. Magadum (Institute of Advanced Engineering and Science, 2026)
This study presents a microcontroller-based fuzzy logic control method for maximum power point tracking (MPPT) in photovoltaic systems under varying temperature and solar irradiation. The proposed controller is implemented on an 8-bit microcontroller and regulates the duty cycle of a pulse-width-modulation-driven DC-DC converter to extract maximum power from the photovoltaic array. Unlike conventional MPPT methods, the fuzzy logic approach provides faster response, improved flexibility, and stronger robustness against nonlinear current-voltage characteristics and converter switching effects. The system includes a photovoltaic array, sensing circuits, a DC-DC converter, and an embedded controller programmed with optimized C code for real-time operation. Experimental results show that the proposed method reaches the maximum power point quickly and maintains stable performance during environmental changes. It also improves energy conversion efficiency compared with traditional algorithms. Its low-cost hardware and simple embedded implementation make it suitable for practical photovoltaic applications and sustainable energy generation in renewable energy systems.